Diagnosis and prognostic value of markers of oncogenesis in patients with hyperplastic endometrial processes with uterine fibroids - Krut, Yu. Ya.; Zemlyana, N. A.; Savchenko, S. E.; Круть, Юрій Якович; Земляна, Наталія Анатоліївна; Савченко, С. Е. (My University, 2020)
Introduction: The relevance of the study of the problem of endometrial hyperplastic processes (EHP) is due primarily to the high risk of malignancy of this pathology and its recurrent course. Despite numerous studies on EHP, some issues of pathogenesis, diagnosis and treatment of this pathology remain debatable. Objective: To evaluate the levels of APRIL, survivin and phosphoPTEN in serum of women with various forms of EHP in combination with uterine fibroids and their prognostic value for recurrence.Materials and Methods: 105 women with endometrial hyperplastic processes and endometrial adenocarcinoma were examined during the study. The first group consisted of 34 women with simple endometrial hyperplasia without atypia (SEHWA), the second group included 47 patients with complex endometrial hyperplasia without atypia (CEHWA). The groups were divided into subgroups with or without uterine fibroids. The third group consisted of 26 women with endometrial adenocarcinoma. Results: Level of APRIL was increased in the CEHWA group compared to the control group (p<0,05) and the SEHWA (p<0,05). Women with endometrial adenocarcinoma had significantly higher APRIL levels compared to controls and patients with both types of endometrial hyperplasia (p<0,05). Women with SEHWA had significantly higher level of survivin compared to controls (p<0,05). Patients with CEHWA and adenocarcinoma had serum levels of survivin higher than those in the control and SEHWA groups (p<0,05). Conclusions: Adequate prognostic significance for the occurrence of relapses of EHP had the increasing of APRIL level greater than 43 pg/ml and survivin level greater than 70 pg/ml. In patients with EHP in combination with uterine fibroids a significant risk factor for relapse was an increasing of APRIL level greater than 43 pg/ml.
Keywords: endometrial hyperplastic processes; uterine fibroids; biomarkers; survivin